1995
DOI: 10.1073/pnas.92.22.10089
|View full text |Cite
|
Sign up to set email alerts
|

Nramp defines a family of membrane proteins.

Abstract: Nramp (natural resistance-associated macrophage protein) is a newly identified family of integral membrane proteins whose biochemical function is unknown. We report on the identification of Nramp homologs from the fly Drosophila melanogaster, the plant Oryza sativa, and the yeast Saccharomyces cerevisiae. Optimal alignment of protein sequences required insertion of very few gaps and revealed remarkable sequence identity of28% (yeast), 40% (plant), and 55% (fly) with the mammalian proteins (46%, 58%, and 73% si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
230
0
5

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 315 publications
(238 citation statements)
references
References 34 publications
3
230
0
5
Order By: Relevance
“…9,14,17 Nramp1 is part of an ancient family of proteins with highly conserved members in mammals, birds, invertebrates, plants, fungi and even bacteria. [18][19][20][21][22][23][24][25][26] Nramp1 is an integral membrane phosphoglycoprotein located in the late endosome/lysosome compartment of resting macrophages and is recruited to the phagosomal membrane during phagosome maturation 27 that encodes for a divalent-cation transporter. 28 Several additional loci have been found to exert some control during the late phase of infection through their effects on the acquired immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…9,14,17 Nramp1 is part of an ancient family of proteins with highly conserved members in mammals, birds, invertebrates, plants, fungi and even bacteria. [18][19][20][21][22][23][24][25][26] Nramp1 is an integral membrane phosphoglycoprotein located in the late endosome/lysosome compartment of resting macrophages and is recruited to the phagosomal membrane during phagosome maturation 27 that encodes for a divalent-cation transporter. 28 Several additional loci have been found to exert some control during the late phase of infection through their effects on the acquired immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…28 It is possible that Ndfips serve in an adapter role in Notch regulation. dNdfip may facilitate E3 access to Notch, as it interacts with both dNedd4 and Su(dx) and colocalizes with Notch in wing discs and in S2 cells stably 29 Indeed we have observed such a role for dNdfip in the promotion of ubiquitination of Malvolio, 30 the ortholog of the known Ndfip-regulated iron transporter DMT1 (our unpublished observations). 20 Another possible regulatory mode of action for dNdfip may include the direct activation of Nedd4 family E3s, as has been observed for Ndfip2 that promotes the auto-activation of several E3s, including Itch.…”
Section: Discussionmentioning
confidence: 93%
“…43,44 Comparative sequence analysis of the Nramp gene family suggested that Nramp1 functions as a divalent cation transporter. 45 Kinetic studies demonstrated that Nramp1 transports cations out of the phagosomes, and, consequently, 6 .…”
Section: Discussionmentioning
confidence: 99%